Kolaviron and selenium reduce hydrogen peroxide-induced alterations of the inflammatory response - Tebekeme Okoko (Journal of Genetic Engineering and Biotechnology, 2018)
The abilities of kolaviron and selenium (either separately or in combination) to prevent hydrogen peroxide-induced alterations in cell viability and activation were investigated. The cell line U937 was incubated with the antioxidants (i.e. kolaviron or selenium) for 24 h before exposure to hydrogen peroxide and cell viability was assessed via trypan blue dye exclusion assay. The U937 cells were also transformed to the macrophage form, incubated with the antioxidants before exposure to hydrogen peroxide. Subsequently, production of nitric oxide and pro-inflammatory cytokines were assessed as indices of macrophage activation. The myoblast cell line H9c2 was also incubated with Se and kolaviron for 24 h before exposure to hydrogen peroxide. Cell viability and generation of reactive oxygen species (ROS) were assessed via MTT and DCHF assays. The results revealed that hydrogen peroxide significantly reduced (p < 0.05) the viability of U937 cells which was ameliorated by kolaviron and selenium. Kolaviron and selenium also reduced hydrogen peroxide-induced secretion of nitric oxide, TNF-α, IL-1 and IL-6 by transformed U937 cells. Hydrogen peroxide also significantly reduced (p < 0.05) the viability of H9c2 cells which was significantly restored by kolaviron. Though selenium had no effect on the proliferation of H9c2 cells, co-treatment with kolaviron significantly reduced hydrogen peroxide-induced alterations. Both kolaviron and selenium also reduced hydrogen peroxide-mediated ROS production by H9c2 cells. In all cases, the combined action of kolaviron and selenium offered greater amelioration of the hydrogen peroxide-induced alterations than their separate effects (p < 0.05) but may not be synergistic or additive. Keywords: Kolaviron, Selenium, Antioxidants, Nitric oxide, Hydrogen peroxide, Cytokines